Listing, impact assessment and prioritization of introduced land snail and slug species in Indonesia. (20th December 2018) - Nurinsiyah, Ayu Savitri; Hausdorf, Bernhard
Abstract: As the basis for an assessment of the impact of introduced land snail and slug species in Indonesia, we provide a list of these species and specify their distribution in Indonesia, their native range, their habitats and their earliest recorded occurrence in Indonesia. We focus in particular on Java, but also provide data for other parts of Indonesia. Fifteen land snail and slug species occurring in Indonesia are considered introduced. These introduced species are represented in Indonesia by multiple self-sustaining populations in the wild and, thus, are classified as invasive. Using a generic scoring system, we assess the impact of these species with regard to natural environments and to socio-economic issues. Based on this, we suggest a preliminary prioritization for invasive species. We show that Laevicaulis alte, Sarasinula plebeia, Bradybaena similaris and Lissachatina fulica have the highest negative impact scores. This is mainly because of their impact on agriculture and their possible importance as intermediate hosts of the rat lungworm ( Angiostrongylus cantonensis ), a parasite causing eosinophilic meningitis in humans. In order to fulfil one of the targets of the Strategic Plan for Biodiversity 2011–2020, we outline possible measures to control priority species. Finally, we discuss the different scoring systems used for assessing the impacts of introduced species.